LIFE CYCLE ASSESSMENT OF GRANULATED COCONUT SUGAR PRODUCTION FARMERS LEVEL IN PURWOREJO - Rizki, Fajar; Ismayana, Andes; Yani, Moh (Jurnal Teknologi Industri Pertanian, 2025)
Granulated coconut sugar is a powdered coconut sugar manufactured by Purworejo farmers from the sap of the coconut. Farmers' usage of simple technologies is the primary cause of environmental problems due to poor efficiency levels and uncontrolled emission emissions. The objectives of this research were to identify the stages of the granulated coconut sugar production farmer level process, from coconut sap to farmers' granulated coconut sugar, and then analyze the total environmental impact of granulated coconut sugar production farmer level process using the Life Cycle Assessment (LCA) approach and the CML-IA Baseline calculation method. The study's scope included an inventory of "gate-to-gate" inputs and outputs, computation of each stage of the process from sap heating to granulated coconut sugar, and interpretation of the calculation results. The amount of impact created per 1 kg of farmer-produced coconut sugar was employed as the unit of function in the analysis of the consequent environmental impact. SimaPro 9.4.0.2 software was used to calculate environmental impact analysis. The GWP impact of manufacturing 1 kilogram of farmer granulated coconut sugar was 4.76E-02 kg CO2 eq, the AP impact was 9.45E-04 kg SO2 eq, and the EP impact was 2.77E-04 kg PO4 eq. The biggest GWP effect contribution indicator was the use of LPG, which was 2.89E-02 kg CO2 eq, while the largest AP and EP impact contribution indicator was the use of firewood, which was 8.16E-04 kg SO2 eq and 2.12E-04 kg PO4 eq. The improvement scenario of the granulated coconut sugar production farmer level process, namely substituting the use of firewood with rice husks, reduces 85% of the total AP impact and reduces 93% of the total EP impact. Keywords: environmental impact, granulated coconut sugar, life cycle assessment, SimaPro